A Survey on Enhanced Routing Protocol for Underwater Sensor Networks - Mithun Kumar, K; Varaprasada Rao, P (International Journal of Computer Sciences and Engineering, 2025)
Opportunistic void avoidance routing (OVAR) convention has been proposed for UWSNs. It is an any cast, geographic and entrepreneurial steering convention. Expanding consideration has as of late been given to underwater sensor networks (UWSNs) due to their capacities in the sea checking and asset revelation. UWSNs are looked with changed difficulties, the most remarkable of which is maybe how to proficiently convey parcels considering the majority of the limitations of the accessible acoustic correspondence channel. The proposed an improved directing convention, called opportunistic void avoidance routing (OVAR). This address the void issue and the vitality unwavering quality exchange off in the determination of sending set. OVAR exploits disseminated beaconing, builds the contiguousness chart at each jump and chooses a sending set that holds the best exchange off amongst unwavering quality and vitality proficiency. The one of a kind highlights of OVAR in choosing the hopeful nodes in the region of each different prompts the determination of the concealed node issue.